What Factors Should Muzakki Know Before Paying Zakat - Kiki Razroma Yantika; Iiz Izmuddin; Widi Nugraha (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this research is to see what factors must be known by muzakki before paying zakat. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others (Sutrisno Hadi 1987). The form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe what factors must be known by the muzakki before paying zakat. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on factors that can affect muzakki. The result of this research is that trust will be obtained when a person feels comfortable in communicating, and other things, and when they can see firsthand the practice that their opponent is doing. Likewise, the trust of the muzakki in the professionalism displayed in BAZNAS, such as technology, conditions and adequate facilities will make the muzakki more comfortable in distributing their zakat to BAZNAS because they have met the criteria according to their expectations.